Propuesta de rediseño del sistema de control del generador de gases calientes del molino de puzolana - Fernández-Fernández, Leonardo (Instituto Tecnológico de Costa Rica, 2017)
The way Holcim does the things are as important as what they do, so is especially important to know the specific operation of all the systems to bring future improvements in production. To Holcim, the system of regulation of the hot gas generator from the pozzolana mill is the only one which they don’t know its total operation and which they can’t change due to the dependence’s conditions that the company Pillard left them, Pillard was the system’s implementer. A whole operation’s research was developed, information’s collection and characterization of the system leaves Holcim in a state of more knowledge, with the possibility of migration towards new possibilities of modernization. The fact that the actual operation had to be analyzed for a description gave an advantage which led a faults and efficiency analysis and the opportunity to make improvements for recommendations. These improvements became the basics for the proposal of a redesign including new equipment, that was all part of the combustion enhancement, making the system smarter and more efficient.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Combustión; Control; Sensores; Eficiencia; Sistemas; Research Subject Categories::TECHNOLOGY::Engineering mechanics